Pemberdayaan Masyarakat Melalui Pemanfaatan Pekarangan Rumah Menuju Kedaulatan Pangan bagi Jamaah Tani Muhammadiyah Provinsi Riau - Jupendri, Jupendri; Nurrahmi, Nurrahmi; Vernando, Yulio (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to enhance the knowledge and skills of members of the Muhammadiyah Farmers Congregation (JATAM) in Riau Province in utilizing home yards for vegetable cultivation as a step toward achieving food sovereignty. The implementation methods included training and mentoring. Evaluation instruments used consist of pre-test and post-test questionnaires to measure participants’ knowledge improvement, interviews to explore perceptions and motivations, observations to assess participation and practical skills. Quantitative data were analyzed descriptively and using the Paired Sample t-Test, while qualitative data were analyzed using a thematic analysis approach. The results of this community service activity showed increased knowledge and skills among JATAM members in utilizing their home yards for vegetable cultivation, including the ability to select suitable crops, prepare planting media, maintain, harvest, and manage the produce effectively. It is expected that through this program, JATAM can contribute to building food sovereignty within the community.